Adverse childhood experiences and problematic media use: the roles of attachment and impulsivity. Issue 4 (1st October 2020) - Wilke, Nicole; Howard, Amanda Hiles; Morgan, Meredith; Hardin, Martha
ABSTRACT: Research has found that childhood adversity is associated with numerous maladaptive outcomes, including insecure attachment, mental health challenges, and problematic media use. As attachment is a primary developmental process that can be affected by childhood adversity, insecure attachment may be one psychological mechanism through which childhood adversity is associated with problematic media use. Further, disturbances in the attachment relationship resulting from childhood adversity may be associated with increased impulsivity, a construct that has been connected with problematic media use. Using a sample of adults (n = 616), this study examined whether the relationship between adverse childhood experiences and problematic media use was mediated through (i) attachment anxiety, (ii) attachment avoidance, or (iii) both attachment dimensions operating in series with impulsivity. Results revealed that a history of adverse childhood experiences was significantly associated with more problematic media use. Both anxious and avoidant attachment dimensions independently mediated the relationship between adverse childhood experiences and problematic media use. Specifically, avoidant attachment was associated with less problematic media use, and anxious attachment was associated with more problematic media use. Avoidant attachment and impulsivity in series, as well as anxious attachment and impulsivity in series, both accounted for part of the relationship between adverse childhood experiences and problematic media use. Results suggest that attachment may influence media use both directly and indirectly. Implications are discussed.